Parametric computational simulations of unipore cellular structure subjected to compressive loading - Santos, Daniela Sofia Martins dos (2013)
The thesis study focuses on behaviour of a newly developed cellular UniPore structure with unidirectional pores under transversal and longitudinal loading. The computational model of the cellular structure was based on reconstructed irregular geometry of the manufactured specimens and analysed using ABAQUS. The mechanical properties have been studied using parametric computational simulations considering several material and geometrical parameters. Numerical tests provide data of compressive behaviour of UniPore structures and mechanical properties, such as elastic modulus or yield strength.